KESETIMBANGAN AIR SUB DAS KARANGMUMUS DI KOTA SAMARINDA - Ismail, Ismail (UI Scholars Hub, 2009)
Water Balance Analysis at Karangmumus River Basin Area (RBA) Samarinda City. Karangmumus RBA to getting degradation pressure being concrete drying and flooding so much to frighten. Climate data from BMG Temindung and SPAS Lempake has to water balance analysis based on Hewlett and Nutter methode. This region have the Area Class III (1500–2000 mm/year). With the bimodel or double wave rainfall models with C patern. The hight rainfall depth periode at December and April, therefore the low rainfall depth at September and November. Have level Q = ± 9.9%, or rainfall tipe A (very wet area with tropical wet vegetation) and E1 agroclimte zone. Water balance monthly indicated that this area have to water surplus 8 month, i.e. January (27.0 mm), February (57.3 mm), March (119.7 mm), April (72.8 mm), May (48.4 mm), Juni (19.6 mm), November (58.7 mm) and December (75.3 mm), or total amounts water surplus 478.8 mm/year. The water deficits at Juni (0.4 mm), July (0.3 mm), Augus (3.9 mm), September (13.6 mm) and October (26.7 mm) or total amount water deficits (44.5 mm/year).